Randomized controlled trial of the effects of remote ischemic preconditioning on children undergoing cardiac surgery: first clinical application in humans. - Cheung, M; Kharbanda, R; Konstantinov, I; Shimizu, M; Frndova, H; Li, J; Holtby, H; Cox, P; Smallhorn, J; Van Arsdell, G; Redington, A (2006)
OBJECTIVES: We conducted a randomized controlled trial of the effects of remote ischemic preconditioning (RIPC) in children undergoing repair of congenital heart defects. BACKGROUND: Remote ischemic preconditioning reduces injury caused by ischemia-reperfusion in distant organs. Cardiopulmonary bypass (CPB) is associated with multi-system injury. We hypothesized that RIPC would modulate injury induced by CPB. METHODS: Children undergoing repair of congenital heart defects were randomized to RIPC or control treatment. Remote ischemic preconditioning was induced by four 5-min cycles of lower limb ischemia and reperfusion using a blood pressure cuff. Measurements of lung mechanics, cytokines, and troponin I were made pre- and postoperatively. RESULTS: Thirty-seven patients were studied. There were 20 control patients and 17 patients in the RIPC group. The mean age and weight of the RIPC and control patients were not different (0.9 +/- 0.9 years vs. 2.2 +/- 3.4 years, p = 0.4; and 6.9 +/- 2.9 kg vs. 11.5 +/- 10 kg, p = 0.06). Bypass and cross-clamp times were not different (80 +/- 24 min vs. 88 +/- 25 min, p = 0.3; and 55 +/- 13 min vs. 59 +/- 13 min, p = 0.4). Levels of troponin I postoperatively were greater in the control patients compared with the RIPC group (p = 0.04), indicating greater myocardial injury in control patients. Postoperative inotropic requirement was greater in the control patients compared with RIPC patients at both 3 and 6 h (7.9 +/- 4.7 vs. 10.9 +/- 3.2, p = 0.04; and 7.3 +/- 4.9 vs. 10.8 +/- 3.9, p = 0.03, respectively). The RIPC group had significantly lower airway resistance at 6 h postoperatively (p = 0.009). CONCLUSIONS: This study demonstrates the myocardial protective effects of RIPC using a simple noninvasive technique of four 5-min cycles of lower limb ischemia and reperfusion. These novel data support the need for a larger study of RIPC in patients undergoing cardiac surgery.